Comprehensive assessment of slope stability in residual soil slopes - Rahardjo, Harianto (2011)
A brief overview of the principles of unsaturated soil mechanics for solving geotechnical problems is presented with field experiments to illustrate their applications in practice. Fully instrumented residual soil slopes of Bukit Timah Granite and sedimentary Jurong Formation in Singapore were studied. The differing characteristics of pore-water pressure responses, shear strength and factor of safety variation in these residual soil slopes during rainfall are discussed and compared.